2006
DOI: 10.1037/0022-0167.53.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor cultural responsiveness and unresponsiveness in cross-cultural supervision.

Abstract: Thirteen supervisees' of color and 13 European American supervisees' experiences of culturally responsive and unresponsive cross-cultural supervision were studied using consensual qualitative research. In culturally responsive supervision, all supervisees felt supported for exploring cultural issues, which positively affected the supervisee, the supervision relationship, and client outcomes. In culturally unresponsive supervision, cultural issues were ignored, actively discounted, or dismissed by supervisors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 19 publications
7
132
0
Order By: Relevance
“…Multicultural training deficiencies also likely contribute to a lack of cultural awareness by supervisors, which in turn has been shown to negatively impact the multicultural supervisory relationship (Burkard et al 2006). Indeed, lack of cultural awareness by supervisors was viewed as a negative critical incident by supervisees that contributed to weaker appraisals of the supervisor-supervisee relationship (Toporek et al 2004).…”
Section: Training and Supervisionmentioning
confidence: 95%
See 3 more Smart Citations
“…Multicultural training deficiencies also likely contribute to a lack of cultural awareness by supervisors, which in turn has been shown to negatively impact the multicultural supervisory relationship (Burkard et al 2006). Indeed, lack of cultural awareness by supervisors was viewed as a negative critical incident by supervisees that contributed to weaker appraisals of the supervisor-supervisee relationship (Toporek et al 2004).…”
Section: Training and Supervisionmentioning
confidence: 95%
“…Indeed, lack of cultural awareness by supervisors was viewed as a negative critical incident by supervisees that contributed to weaker appraisals of the supervisor-supervisee relationship (Toporek et al 2004). Moreover, Burkard et al (2006) found that when supervisees encountered a culturally unresponsive supervisor, they disclosed less to their supervisor and were instead more likely to go to other students and practitioners for advice and informal supervision regarding their clients. As a result, supervisees may perceive supervisors as culturally unresponsive.…”
Section: Training and Supervisionmentioning
confidence: 95%
See 2 more Smart Citations
“…With the brevity in which multicultural counseling is presented, usually multicultural supervision is not addressed. This lack .of exposure t.o multicultural-c-ounseling educati.on can cause supervisors to not feel confident in addressing multicultural issues (Gatmon et al, 2001) leading to the av.oidance of discussing multicultural issues with supervisees (Burkard et al, 2006). In addition, education can build supervisors awareness of their attitudes towards diversity…”
Section: Barriers To Multicultural Supervisionmentioning
confidence: 99%